PERLINDUNGAN HUKUM BAGI ANAK DALAM KASUS BULLYING MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK DI INDONESIA - Tri Rizky Analiya; Ridwan Arifin (Journal of Gender and Social Inclusion in Muslim Societies, 2022)
Cases of bullying on children are still rampant in Indonesia. Many of these cases occur in the school environment, even with the rapid flow of information, bullying cases also often occur online. This study aims to analyze the legal protection for children provided by the Government through Law Number 35 Year 014 concerning Child Protection in cases of bullying. This study uses a normative juridical approach, where the study covers various related legal regulations. This study found that cases of child abuse in which the perpetrator and victim are children have special mechanisms for handling them. Children as legal subjects have different characteristics through Juvenile Criminal Law and Juvenile Justice. However, a psychological and familial approach is needed in dealing with cases of child bullying.